English Self-Assessment Based on Pluralism in Preventing Radicalism - Andriyani, Santi; Yulistianti, Hayu Dian; Saidah, Nusrotus (IJET (Indonesian Journal of English Teaching), 2019)
The practice of radicalism in Indonesia has increased among all age groups included adolescents. The study found that adolescents or the young generation are mostly affected by radicalism and extremism. The aim of this study is to find out the implementation of English Self-Assessment Based on Pluralism in Preventing Youth Radicalism. This study uses a descriptive analysis method. The instrument of this study is students’ self-assessment worksheet focused on pluralism materials. Based on the analysis conducted, it can be concluded that by implementing English Self-Assessment rubric, the religious understanding of the students is good criteria.